2011
DOI: 10.1371/journal.pone.0016357
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Mesophotic Megabenthic Assemblages of the Vercelli Seamount (North Tyrrhenian Sea)

Abstract: The biodiversity of the megabenthic assemblages of the mesophotic zone of a Tyrrhenian seamount (Vercelli Seamount) is described using Remotely Operated Vehicle (ROV) video imaging from 100 m depth to the top of the mount around 61 m depth. This pinnacle hosts a rich coralligenous community characterized by three different assemblages: (i) the top shows a dense covering of the kelp Laminaria rodriguezii; (ii) the southern side biocoenosis is mainly dominated by the octocorals Paramuricea clavata and Eunicella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 55 publications
6
100
1
1
Order By: Relevance
“…Primers used for the PCR amplifications are listed in Table S2 (in the Supplement). The 18S rDNA gene was amplified using the primer sets 18S1/18S2 (Borchiellini et al, 2001). If nothing was obtained in the first (external) PCR, re-amplification was performed in two overlapping fragments using the primer-pairs 18S1/18S6 and 18S3/18S2.…”
Section: Molecular Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Primers used for the PCR amplifications are listed in Table S2 (in the Supplement). The 18S rDNA gene was amplified using the primer sets 18S1/18S2 (Borchiellini et al, 2001). If nothing was obtained in the first (external) PCR, re-amplification was performed in two overlapping fragments using the primer-pairs 18S1/18S6 and 18S3/18S2.…”
Section: Molecular Identificationmentioning
confidence: 99%
“…Due to its inaccessibility by scuba diving, until recently it was therefore one of the less-studied habitats in the ocean (Lesser et al, 2009). Thus, basic information on the mesophotic sponge communities, including community composition, species depth range, habitat preferences, and species abundance and distribution, are scarce worldwide (Bo et al, 2011;Schönberg et al, 2012;Olson et al, 2013;Slattery et al, 2015). Furthermore, the processes that structure these communities are virtually unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Sheltered hydrodynamic conditions naturally increase the abundance of active, rather than passive, filter-feeders, favouring thus the dominance of various species of sponges and ascidians (Bo et al, 2011); many such species have been shown to contain some of the most bioactive chemicals, providing, thus, useful insight to pharmaceutical research (Uriz et al, 1991). Sheltered conditions also increase human access and activities, rendering these communities more popular to recreational and professional fishermen, as well as scuba divers.…”
Section: Mediterranean Coralligenous Communities Sheltered From Hydromentioning
confidence: 99%
“…The high global abundance of seamount ecosystems still represents an immense challenge to scientists, thus it is somewhat unsurprising that < 0.3 % have been sampled biologically in any detail, despite significant interest in these features (Ramirez-Llodra et al, 2010). Seamounts are often typified by highly rich and diverse communities of predominantly large suspension feeding organisms such as gorgonians and antipatharian corals, which are often the focus of seamount research (Bartsch, 2008;McClain et al, 2009;Clark et al, 2010;McClain, 2010;Rowden et al, 2010;Simpson and Watling, 2010;Bo et al, 2011;Sautya et al, 2011;Tracey et al, 2011). Many studies have also concentrated upon seamount fish populations (Clark, 1999;Matthiesson et al, 2002;Diekmann, 2006;Christiansen et al, 2009a;Menezes et al, 2009;Morato et al, 2009;Hirch and Christiansen, 2010) with relatively few focussed upon the infauna Dauvin, 2000, 2003;Richer De Forges et al, 2000;Koslow et al, 2001;Surugiu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%